2021
DOI: 10.4103/2305-0500.306437
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium supplementation, clarified egg yolk extender and slow cooling improve cryopreserved sperm characteristics of Saanen buck

Abstract: Objective: To evaluate the effect of cooling rates, selenium supplementation, and three semen extenders on cooled and frozen-thawed Saanen buck sperm. Methods: Twenty Saanen bucks were divided into two groups: the selenium supplemented group and the control group. Ejaculates were collected once weekly by artificial vagina. The first experiment examined the effects of cooling rates and selenium supplementation on semen characteristics of Saanen bucks. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In the current study, groups receiving 1 µg/mL of cysteamine loaded on Se-NPs and Se-NPs synthesized using bacteria had lower abnormalities and malondialdehyde levels in spermatozoa cells than other treatment groups, and these results are consistent with those of Lukasa et al 47 . investigated cooling and freezing, which showed that selenium was significantly protective against lipid peroxidation (production of malondialdehyde) on sperm parameters 47 . Furthermore, Natiq et al 48 reported that Se-NPs treated with 1 and 2 µg/mL had lower malondialdehyde levels than the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, groups receiving 1 µg/mL of cysteamine loaded on Se-NPs and Se-NPs synthesized using bacteria had lower abnormalities and malondialdehyde levels in spermatozoa cells than other treatment groups, and these results are consistent with those of Lukasa et al 47 . investigated cooling and freezing, which showed that selenium was significantly protective against lipid peroxidation (production of malondialdehyde) on sperm parameters 47 . Furthermore, Natiq et al 48 reported that Se-NPs treated with 1 and 2 µg/mL had lower malondialdehyde levels than the control group.…”
Section: Discussionsupporting
confidence: 92%